The Seroprevalence of Hepatitis C Virus (HCV) in Hemodialysis Patients in Oman: A National Cross-Sectional Study - Intisar Al Shukri; Adil Al Wahaibi; Hanan Al kindi; Yaqoub Al-Maimani; Amal Al Maani; Abdullah Alqayoudhi; Mersum C. Methew; Jini Pradeesh; Raiya Al Abrawi; Abdo Debs; Nabila Mansoor; Ahmed AlRahbi; et al. (Springer, 2023)
Abstract Background HCV infection in hemodialysis units is a significant cause of morbidity and mortality. The risk of HCV infection among dialysis patients is higher compared to the general population due to high potential blood exposures in hemodialysis settings. This study aims to assess the national HCV seroprevalence in selected dialysis units and to determine the risk factors for acquiring HCV infection. Methods This cross-sectional study was conducted from 1 January to 31 March 2021. A total of 734 patients from 11 hemodialysis centers in Oman were included. Samples were tested simultaneously for HCV antibodies and HCV RNA. HCV genotyping was determined in all viremic patients. Demographic and hemodialysis center related data were gathered and their association with the positive HCV serology were explored using univariate and multivariate logistic regression analysis. Results Out of 800 patients selected from 11 dialysis units for the study, 734 patients (91.8%) were included. The overall seroprevalence of HCV infection among hemodialysis patients was 5.6%. (41/734). HCV RNA was detected in 31.7% (13/41) of seropositive hemodialysis patients. The most common genotype was subtype 1a, followed by subtype 3. Variables associated with high HCV prevalence were family history of HCV and duration of dialysis. Conclusion The prevalence of infection within hemodialysis patients in Oman has significantly decreased but remained higher than the general population. Continuous monitoring and follow-up, including periodic serosurvey and linkage to care and treatment are recommended. Additionally, practice audits are recommended for identifying gaps and ensuring sustainability of best practices and further improvement.